Expression profile of immunological and vascular mediators in an unusual case of paravertebral primary cutaneous non-Hodgkin lymphoma - Jeane Sousa Ribeiro; Uener Ribeiro dos Santos; Izaltina Silva-Jardim; Jane Lima dos Santos; Juneo Freitas Silva (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2020)
Primary cutaneous follicle center lymphoma (PCFCL) is a rare type of indolent, low-grade cutaneous B-cell lymphoma, most frequent in trunk, particularly the head and scalp. Differential diagnosis for exclude other pathologies is needed. Here, we describers a detailed analysis on the expression profile of immunological and vascular mediators in tumor microenvironment that contribute to the knowledge, prognostic and diagnostic aid in a rare case of paravertebral PCFCL mimicking clinical appearance and localization of an unusual sebaceous cyst in a 48-year-old woman without history of neoplasia.